Skeletal Aging and Osteoporosis Biomechanics and Mechanobiology - Silva, Matthew J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The focus of this book is on mechanical aspects of skeletal fragility related to aging and osteoporosis. Topics include: Age-related changes in trabecular structure and strength; age-related changes in cortical material properties; age-related changes in whole-bone structure; predicting bone strength and fracture risk using image-based methods and finite element analysis; animal models of osteoporosis and aging; age-related changes in skeletal mechano responsiveness; exercise and physical interventions for osteoporosis.
Age-related changes in trabecular structure and strength -- Age-related changes in cortical material properties -- Age-related changes in whole-bone structure -- Predicting bone strength and fracture risk using image-based methods and finite element analysis -- Animal models of osteoporosis and aging -- Age-related changes in skeletal mechanoresponsiveness -- Exercise and physical interventions for osteoporosis.
Keywords: Engineering; Human physiology; Orthopedics; Materials; Biomedical engineering; Biomaterials; Engineering; Biomedical Engineering; Biomaterials; Human Physiology; Conservative Orthopedics; Continuum Mechanics and Mechanics of Materials